Study of The Vegetation on The Sandy Coastal in Daryanah Region, Easteren Libya - Elfarse, Muftah; Al Borkr, Abd El-Nasser; Alzerbi, Abdulhamid; Mohammed, Jihan Farag (The 1st International Conference On Basic Sciences & Its Applictionss, 2024)
This study aims to identify the types of plants that make up the vegetation of the sandy coastal in the area of Daryanah and identify the most important human activities affecting the diversity of vegetation, where 30 species growing naturally in the coastal such as sand dunes, these species belong to 29 genera and distributed on 21 families belong to angiosperms, and these species are exposed to various human activities, the most important of which are urban sprawl, sand dredging and the establishment of tourist facilities, which cause pressure on these species and threaten their existence in the region. The maximum number of species were of family Amaranthaceae with four species, followed by family Asteraceae and Fabaceae three species each, then the Euphorbiaceae and Poaceae two species each.